2018
DOI: 10.1088/1742-6596/972/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Stray light correction of array spectroradiometer measurement in ultraviolet

Abstract: Abstract. For most of the array spectroradiometer, stray light is significant in UV band. Stray light correction of a UV array spectroradiometer is investigated using optical filters. If a group of filters with continuous bandpass are chosen, stray light contribution due to all the bands can be obtained using a numerical algorithm. The array spectroradiometer with the stray light corrected is used to measure the spectral irradiance of several UV lamps. The measurement results are compared to a double monochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The customary traceability chain of a spectroradiometer usually involves calibration through lamps (e.g., in the laboratory), followed by independent comparison with a reference instrument (in the field). However, as shown by previous studies [67][68][69], incandescence lamps, such as those used in our current setup, are not the best way to calibrate the AvaSpec. Indeed, their emittance in the UV region is very low, and the sensitivity of the array spectroradiometer in the same range is also very weak; therefore, only low and noisy signals are expected.…”
Section: Absolute Irradiance Calibrationmentioning
confidence: 80%
See 2 more Smart Citations
“…The customary traceability chain of a spectroradiometer usually involves calibration through lamps (e.g., in the laboratory), followed by independent comparison with a reference instrument (in the field). However, as shown by previous studies [67][68][69], incandescence lamps, such as those used in our current setup, are not the best way to calibrate the AvaSpec. Indeed, their emittance in the UV region is very low, and the sensitivity of the array spectroradiometer in the same range is also very weak; therefore, only low and noisy signals are expected.…”
Section: Absolute Irradiance Calibrationmentioning
confidence: 80%
“…Indeed, as discussed in Section 3.1.5, the use of incandescence lamps to calibrate array spectroradiometers in regions of weak sensitivity, such as UV and IR [68,69], is problematic with our current system. The latter can certainly be improved in the future, e.g., by employing optical cut-off filters [16,48,67], and thus reducing the infrared component of the irradiance, or even by using completely different light sources, such as LEDs [79] (stability requirements in absolute calibrations would exclude deuterium lamps from the choice [22]). However, we also demonstrated that the response can be determined by transfer once for all (or with a rather low frequency), and then tracked this through the use of 200 W lamps in a relative way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation